Pbl implementation: an experience of the faculty of computer science and information technology, University of Malaya - Mokhtar, S.; Bakar, Z.A. (2004)
This paper describes the experiences of implementing Problem-based Learning (PBL) in the field of Computer Science and Information Technology, at the Faculty of Computer Science &Information Technology, University of Malaya. The implementation strategy that has been adopted is presented. This is followed by an analysis of the students’ and lecturers’ perception of PBL after its initial implementation.